Students’ Conceptions of Bell Curve Grading Fairness in Relation to Goal Orientation and Motivation - TAN Yuen Ling, Lynette; Yuen, Brenda; LOO, Wee Ling; Prinsloo, Christiaan; Gan, Mark (International journal for the scholarship of teaching and learning, 2020)
The controversial bell curve has received considerable attention in recent years as a grade distribution tool where "norm-referenced grading involves comparing students' performances with each other" rather than where they fall on a "predefined continuum of quality" (Brookhart, 2013, p. 258). Despite educators' deep concern on the fairness of bell curve grading, there is little research done on students' conceptions of that grading system in higher education. This correlational study uses open-ended questions and three instruments to measure students' conceptions of the fairness of bell curve grading, their goal orientations, and motivation. Undergraduates from three universities participated in the survey (N= 211). Results suggest that students have a formalized conception of bell curve grading, perceive it to be generally fair, but tend to hold negative views about its impact on learning. The correlations with their goal orientation and levels of motivation, while yielding constructive inferences, were not overly significant.